THE RULING ELITE IN JAPAN : THE IMPACT OF NATIONAL TRADITIONS AND DEMOCRATIC INNOVATIONS - Топалова, С.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
This article explores the characteristics of the formation and functioning of the ruling elite in modern Japan, its main differences from the political elites in Western democracies are illustrated . Was shown the specificity of the combination of political traditions that have been formed on the basis of religious, mythological ground and borrowed from Western culture policies and procedures of  the functioning of the elite.